Optimizing Wealth Care: A Comprehensive Analysis of Sustainable Waste Management Strategies in High-Income Societies - Mohammed Shadab Aslam; Syed Mohd Faisal Qadri (Universitas Efarina, 2023)
This research paper aims to provide a comprehensive analysis of sustainable waste management strategies in high-income societies, with a focus on the wealth care sector. As affluence often correlates with increased consumption and waste generation, there is a pressing need to optimize waste management practices to mitigate environmental impact. The study explores the current state of wealth care waste management, identifies challenges, and evaluates sustainable strategies to promote responsible resource use.